Dakwah Bil Hal in Instilling Religious Awareness in Padanglampe Village Community, Ma'rang District, Pangkep Regency - Andi Hasriani (Journal of Research and Multidisciplinary, 2022)
Dakwah bil hal is one approach to delivering da'wah needed by the community. Although dakwah bil oral can be found everywhere, dakwah bil hal remains a major need. Bil Hal's da'wah is expected to instill religious awareness in the community. The activities of the dakwah bil hal method in instilling religious awareness in the community can be through material or non-material assistance such as giving direct examples to the object of da'wah through example, establishing worship facilities, religious schools, and others. This study discusses the role of dakwah bil hal in instilling diverse awareness for the community located in Padanglampe Village, Ma'rang District. The data collection method used is descriptive qualitative, namely the development of concepts based on existing data, following a flexible research design according to the context. The steps taken are to determine the research location, research subjects, and data collection methods (observations, interviews, documentation. The data analysis (data induction, data deduction, and followed by drawing conclusions. The results show Da'wah bil hal has a very broad scope, such as sharia cooperative activities, organizing public health businesses, organizing education, taklim assemblies, building Islamic schools, Koranic education parks, etc. Dakwah bil hal is a propaganda medium that is always missed by the community because it contains the actions of a preacher who can be used as a role model. People are motivated to do something that is conveyed or exemplified by the preachers. Therefore, a preacher as a power of change must maintain his words and behavior in everyday life, avoiding words and actions that are contrary to his words.